The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5455/ijsm.sutures-versus-staplers-for-skin-closure
|View full text |Cite
|
Sign up to set email alerts
|

Sutures Versus Staplers for Skin Closure of Midline Incision in Laparotomy Patients and Their Outcome

Abstract: Objective: Aim of the study is to compare the clinical outcome of staplers versus skin sutures in skin closure of midline incision in laparotomy patients in term of superficial surgical site of infection, pain, wound dehiscence, time of skin closure and cosmetic satisfaction and thus verify the speed of closure, it is unclear if staples give a superior cosmetic result or reduce pain. Material and Methods: After clearance from ethical committee study was conducted at Punjab Institute of Medical Sciences (PIMS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Wound infection does not show statistical signi icant with P-value of 0.093 1 month after surgery; however, after 6 months, the results of both the methods were similar. They argued that it is advantageous to use sutures with staples in contaminated surgery (Zwart et al, 1989;Kumar, 2017) In the present study, three complications were encountered in the suture group in the form of wound infection. In the stapler group wound infections were absent (Table 4 ) Luiz R Medina dos Santos et al in their study of 20 consecutive patients during head and neck surgery concluded that the use of skin staplers closure saves time by 80%, with better cosmetic results, and does not increase the incidence of infections, although the slightly higher cost was involved (Santos et al, 1995).…”
Section: 0% Groupssupporting
confidence: 44%
“…Wound infection does not show statistical signi icant with P-value of 0.093 1 month after surgery; however, after 6 months, the results of both the methods were similar. They argued that it is advantageous to use sutures with staples in contaminated surgery (Zwart et al, 1989;Kumar, 2017) In the present study, three complications were encountered in the suture group in the form of wound infection. In the stapler group wound infections were absent (Table 4 ) Luiz R Medina dos Santos et al in their study of 20 consecutive patients during head and neck surgery concluded that the use of skin staplers closure saves time by 80%, with better cosmetic results, and does not increase the incidence of infections, although the slightly higher cost was involved (Santos et al, 1995).…”
Section: 0% Groupssupporting
confidence: 44%